Radiocaesium levels in game in the Czech Republic - Škrkal, Jan; Rulík, Petr; Fantínová, Karin; Mihalík, Ján; Timková, Jana (Journal of environmental radioactivity, 2015)
The paper summarizes results of monitoring of (137)Cs activities in game species roaming in the woods over the territory of the Czech Republic for the time interval of 1986-2012. Geometric means and other statistical characteristics were estimated from the data sets on the assumption of log-normal distribution of the data from the time interval 2004-2012 where the character of data distribution had displayed no significant change. Geometric means (in Bq/kg) in meat were: wild boar 5.1, red deer 1.9, roe deer 0.77 and feathered game 0.14. The mean value in the less frequent game amounted to 0.36 Bq/kg. The geometrical standard deviation (GSD) widely varied from 1.6 to 21 for the studied species. Based on mass activity dependence on time, we assessed the effective and environmental half-lives of activity decline. For red deer and roe deer, the effective (137)Cs half-life was 2.9 and 3.2 years, and environmental half-life 3.2 and 3.6 years respectively. The effective half-life of (137)Cs in wild boar of 38 years was determined with large uncertainty and it shows constant influx of (137)Cs activity to the digestive tract of wild boars. A statistically significant season-based (137)Cs level was found in red deer and wild boar. Higher winter and spring activities of (137)Cs in wild boar are linked with decreasing access to naturally occurring food with lower (137)Cs content (chestnuts, acorns, and beech nuts), making boar grub around for ground-deposited food (often for mushrooms with higher activity). Higher winter activities of (137)Cs in red deer meat, most probably, are due to lower access to green diet in winter. The average annual committed effective dose for Czech population based on estimates of game species meat consumption between 2004 and 2012 was insignificant, only 0.03 μSv.
Keywords: Animals; radioizotopy cesia; Česká republika; Cesium Radioisotopes; Soil Pollutants, Radioactive; radioaktivní látky znečišťující půdu; zvířata; prasata; Deer; Swine; Czech Republic; vysoká zvěř